Sedimentological characteristics of the Albiano (Grupo Casma) - Chillón river valley - Jacay Huarache, J. (2002)
Part of the lower Cretaceous of the coastal region of the Central Peru was investigated (region of Lima) conformed by sequences volcanic and volcaniclastic, denominated Casma Group with a numerous amonites fauna, what allows to assign to this series an age Albian - Cenomanian. It is thick volcanic and volcaniclastic series characteristic of a volcanic arch that appear in valley of the Chillon river.